(untitled) (Acta Entomologica Serbica, 2015)
Cynipid gall wasps on Mount Rtanj were faunistically investigated during the period from 2012 to 2015. In the course ofthese investigations, a total of 30 species were recorded, belonging to two tribes (Cynipini and Diplolepidini) and eightgenera (Andricus, 19 species; Cynips, 3; Diplolepis, 2; Neuroterus, 2; Aphelonyx, 1; Dryocosmus, 1; Biorhiza, 1 andPseudoneuroterus, 1). For all of the recorded species, the localities, dates and hosts on which they were found on Mt.Rtanj are given.